2022
DOI: 10.1371/journal.pone.0273459
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing quinoa growth under severe saline-alkali stress by phosphate solubilizing microorganism Penicillium funicuiosum P1

Abstract: Promoting the growth of plants and improving plant stress-resistance by plant growth-promoting microorganism increasingly become a hotpot. While, most researchers focus on their supply role of nutrition or plant hormone. In this study, a novel mechanism that phosphate solubilizing microorganisms promoted plant growth under saline-alkali stress through secretion of organic acids, was proposed. The effects of desulfurization gypsum, humic acid, organic fertilizer and phosphate-solubilizing microorganism Penicill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…Zhang et al [42] found that saline-alkali stress significantly reduced wheat leaf photosynthetic parameters and chlorophyll content, inhibiting their photosynthesis and affecting plant growth. Similar findings have been reported in quinoa [43] and maize [44]. In this study, a simultaneous reduction in Gs and Ci was found.…”
Section: Mt Treatment Effects On Photosynthetic Physiologysupporting
confidence: 92%
“…Zhang et al [42] found that saline-alkali stress significantly reduced wheat leaf photosynthetic parameters and chlorophyll content, inhibiting their photosynthesis and affecting plant growth. Similar findings have been reported in quinoa [43] and maize [44]. In this study, a simultaneous reduction in Gs and Ci was found.…”
Section: Mt Treatment Effects On Photosynthetic Physiologysupporting
confidence: 92%
“…strains can alleviate plant salt stress (Leitão & Enguita, 2016 ) (Table 1 ). This is the case of Penicillium funiculosum P1, which improved the growth of quinoa plants under severe saline‐alkali stress (Jin et al., 2022 ), or a halotolerant endophytic strain of Penicillium chrysogenum which, when inoculated to tomato plants, promoted their growth even though they were irrigated with a 300 mM saline solution for almost 10 weeks (Morsy et al., 2020 ). Similarly, inoculation of lettuce seedlings with two psychrotolerant root‐fungal endophytes, Penicillium brevicompactum KJ881370 and P. chrysogenum KJ881371, isolated from Antarctic plants, enhanced their survival under saline conditions, and also increased drought tolerance and water use efficiency (Molina‐Montenegro et al., 2016 , 2020 ).…”
Section: Fungal Plant Probiotics and Extreme Environmentsmentioning
confidence: 99%